Cognitive performance in people with Parkinson's disease and mild or moderate depression: effects of dopamine agonists in an add-on to L-dopa therapy - Rektorová, I; Rektor, I; Bares, M; Dostál, V; Ehler, E; Fanfrdlová, Z; Fiedler, J; Klajblová, H; Kulist'ák, P; Ressner, P; Svátová, J; Urbánek, K; et al. (European journal of neurology, 2005)
In a randomized prospective multi-centre study, we evaluated the cognitive performances of a group of 41 non-demented patients, all with advanced Parkinson's disease (PD) and a current depressive episode, in whom the effects of pramipexole (PPX) and pergolide (PRG) in an add-on to l-dopa therapy were also studied and published with regard to motor symptoms of PD, motor complications and depression. The Trail Making Test, the Stroop test and four subtests (arithmetic, picture completion, digit symbols and similarities) of the Wechsler Adult Intelligence Scale-Revised were performed prior to and 8 months after the administration of either PPX or PRG. We found no statistically significant difference between the two tested drugs or between the first and the last visit in any of the above-listed neuropsychological tests. All patients' motor outcomes significantly improved and we conclusively demonstrated the anti-depressive effect of PPX. The dissociation of dopaminomimetic effects on the different tested domains indicates that there are different pathological mechanisms of cognitive, motor and affective disturbances in advanced PD patients. In our non-demented group of fluctuating depressed PD subjects, both PPX and PRG administration in combination with l-dopa were safe in terms of the effect on cognitive performance.
Keywords: neparametrická statistika; Humans; Dopamine Agonists; lidé středního věku; Female; Aged; analýza rozptylu; Analysis of Variance; Prospective Studies; senioři; lidé; agonisté dopaminu; levodopa; Cognition Disorders; ženské pohlaví; Male; Middle Aged; Levodopa; Statistics, Nonparametric; Depression; kognitivní poruchy; mužské pohlaví; prospektivní studie; deprese; kombinovaná farmakoterapie; Parkinson Disease; Drug Therapy, Combination; Parkinsonova nemoc